DIVERGÊNCIAS ENTRE O CIMI E A FUNAI NA REGIÃO DO ARAGUAIATOCANTINS ENTRE 1972-1985. - Sales, Orlando Silva (2015)
The present work discusses the of perception changes about indigenist policies over the twentieth century. Therefore, follow an objective by the changes that have occurred in the religious middle starting from middle of last century.Trail by stroked paths since the II Vatican Council that strongly have influenced the Episcopal Conferences in Latin America. Parallel, provides an analysis of of governmental indigenist policies during the beginning of the republican regime in Brazil which defined the modality of the tutelage with the indigenous peoples. For this, crosses the long path performed by the to the Indians Protection Service (SPI), and the sustaining arms that indigenist policies, also known as "rondoniano Indigenism". Is sought at work show The ways, both by the Catholic Church, as by the Brazilian State in the structuring of speech in defense of the indigenous cause. We seek to understand the results of a whole process of taking a position in the area of indigenist policies. On one side, the religious were structuralized around the Indigenist Missionary Council - CIMI and kept a position for renewal of missionary practices. On the other hand, the Brazilian political system that has, to suffer hardening with the advent of civil-military dictatorship, has put in the shock positions defended by the State, hereinafter represented by FUNAI, successor to the SPI and organ responsible for indigenous and CIMI tutelage. This latest has become over the second decade of 1970, the spokesperson of Indian pastoral of the Catholic Church. The clash between them was felt in the mass media and especially the Parliamentary Committee of Inquiry - CPI s Indian and of earth, the National Congress. Lastly the paper will analyze as happened the involvement of the "Church of the Gospel" together with indigenous issues in the Araguaia-Tocantins region. Thus, will be trying to understand the structure of regional CIMI with the indigenous peoples and forms of resistance held in the region on of the border of the expansion fronts.